Karakteristik Inklusi Fluida Endapan Tembaga-Emas Porfiri Brambang Di Pulau Lombok, Indonesia - Aji Syailendra Ubaidillah (PROMINE, 2022)
The type of gold deposit in the research area in Brambang Village, Lombok Island, West Nusa Tenggara can be interpreted from several things, including fluid inclusions.This type of gold deposit is very important to know related to the potential gold deposits in this area. The lithology unit in the Brambang area can be divided into several lithological units considering their lithological dominance: lapilli tuff, diorite, tonalite and diatreme breccia. There are three types of veins observed where there are the fluid inclusions samples are taken, namely vein types A, B and C from the vein zone in tonalite rocks. The results of salinity measurements show two temperature groups that can be adjusted with vein type A-B for a temperature of ~550 oC and vein type C for a temperature of ~250 oC, these temperature magnitudes indicate the type of porphyry mineralization associated with base metals.